ChemInform Abstract: A Simple Phosphine—Diolefin‐Promoted Copper‐Catalyzed N‐Arylation of Pyrazoles with (Hetero)aromatic Bromides: The Case of Chloroarenes Revisited. Issue 11 (8th March 2013) - Rampazzi, Vincent; Massard, Alexandre; Richard, Phillippe; Picquet, Michel; Le Gendre, Pierre; Hierso, Jean‐Cyrille
Abstract The combination of cubane (I)/PPH is found to catalyze the coupling of aryl and heteroaryl bromides with pyrazole (II) and its derivatives (V) under mild conditions.